Biopolymers impact on hygrothermal properties of rammed earth: from material to building scale. (1st April 2023) - Losini, Alessia Emanuela; Grillet, Anne-Cecile; Vo, Linh; Dotelli, Giovanni; Woloszyn, Monika
Abstract: Three biopolymers were tested as rammed earth (RE) stabilizers, evaluating their impact on the hygrothermal behavior from material to building scale. Hygrothermal characterization included the determination of sorption isotherm, water vapor permeability, thermal conductivity at different moisture content, and specific heat capacity. The hygrothermal data were used as input for the simulation at whole-building scale considering combined heat and moisture transfer. The results were evaluated by comparing heating demand, thermal comfort during summer, and the contribution of walls for passively controlling indoor humidity. The results show that hygric properties were only slightly affected by the use of stabilizers, while the thermal conductivity was 33% higher for RE stabilized with lignin, consequently increasing the heating demand at whole-building scale. All RE walls were effective in reducing temperature oscillations in summer. In the particular case of a canicular event, the indoor temperature was reduced by up to 10° compared with the outdoor value. The indoor humidity also benefited from the passive regulation by RE walls, regardless of whether a stablizer was used. Highlights: Stabilization of RE with lignin sulfonate increases thermal conductivity by up to 30%. RE can reduce indoor temperature by up to 10° during canicular events. The use of paint on RE walls decreases their contribution to controlling indoor humidity. Uninsulated RE walls represent approximately 50% of the total sensible heat losses.